2022
DOI: 10.3389/fmicb.2022.988083
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the pharmacokinetics of aflatoxin B1: In vitro determination of Michaelis–Menten constants, intrinsic clearance and the metabolic contribution of CYP1A2 and CYP3A4 in pooled human liver microsomes

Abstract: Mycotoxins, fungal secondary metabolites, are ubiquitously present in food commodities. Acute exposure to high levels or chronic exposure to low levels has an impact on the human body. The phase I metabolism in the human liver, performed by cytochrome P450 (CYP450) enzymes, is accountable for more than 80% of the overall metabolism of exogenous and endogenous compounds. Mycotoxins are (partially) metabolized by CYP450 enzymes. In this study, in vitro research was performed on CYP450 probes and aflatoxin B1 (AF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The formation of AFB1 and AFM1 radicals that react with proteins in the sample is also hypothesized [ 30 ]. Currently, research has been performed on the metabolism of AFB1, both in vitro and in vivo, but more research is a prerequisite to fully assign the observed AFB1 decrease to metabolites [ 25 , 26 , 31 ]. Understanding these interactions is crucial, especially for HIV patients consuming AFB1-contaminated food, as EFV could influence AFB1 immunotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of AFB1 and AFM1 radicals that react with proteins in the sample is also hypothesized [ 30 ]. Currently, research has been performed on the metabolism of AFB1, both in vitro and in vivo, but more research is a prerequisite to fully assign the observed AFB1 decrease to metabolites [ 25 , 26 , 31 ]. Understanding these interactions is crucial, especially for HIV patients consuming AFB1-contaminated food, as EFV could influence AFB1 immunotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were prepared based on the protocol detailed in Lootens et al, 2022 [ 31 ]. In brief, centrifugal Eppendorf cups were filled with 50 µL substrate solution (i.e., 5 µM for AFB1 or 5 µM for MDZ) and with 50 µL of 1.15% KCl or 5 µL of co-substrate EFV (7.9 µM or 250 µM) and 45 µL of 1.15% KCl solution, in case of co-incubation.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro–in vivo extrapolation (IVIVE) is, therefore, the ultimate tool: by performing in vitro experiments on human cells or microsomes, one can determine the metabolic parameters needed to build a PBPK model. In this case, not much data were available for AFB1; therefore, in vitro experiments were performed and certain parameters were predicted based on the physicochemical characteristics of AFB1 [ 31 ]. The model was built using a bottom-up approach without any fitting.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, there was a triphasic effect observed in the 500 mg OPZ group, where no effect was observed in the first month, a decrease in AFB1-adduct formation occurred in the second month of OPZ intake and in the first month post-intervention [87]. Recently, PK parameters of AFB1 were unraveled by Lootens et al, (2022) giving more insight in what happens with AFB1 in the human body [97]. It is clear that more research needs to be performed both in vitro and in vivo to have a better insight in possible interactions between mycotoxins and other compounds, such as drugs.…”
Section: Aflatoxinsmentioning
confidence: 99%